2003
DOI: 10.1042/bss0700095
|View full text |Cite
|
Sign up to set email alerts
|

Control of the expression of inflammatory response genes

Abstract: The expression of genes involved in the inflammatory response is controlled both transcriptionally and post-transcriptionally. Primary inflammatory stimuli, such as microbial products and the cytokines interleukin-1 (IL-1) and tumour necrosis factor α (TNFα), act through receptors of either the Toll and IL-1 receptor (TIR) family or the TNF receptor family. These cause changes in gene expression by activating four major intracellular signalling pathways that are cascades of protein kinases: namely the three mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
89
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 12 publications
1
89
1
1
Order By: Relevance
“…Interestingly, Baltimore and co-workers (31) have suggested that TNF-␣ is expressed by the MyD88-independent pathway via interferon regulatory factor 3, which was time-dependent. Additionally, p38 has been shown to play a role in regulating both TNF-␣ message stability and protein expression (32,33). We have described previously that Mal interaction with TRAF6 mediates Erk1/2 and JNK activation (17), but not p38, which may explain the discrepancy that the MalE190A mutant is still able to induce TNF-␣ expression.…”
Section: Discussioncontrasting
confidence: 39%
“…Interestingly, Baltimore and co-workers (31) have suggested that TNF-␣ is expressed by the MyD88-independent pathway via interferon regulatory factor 3, which was time-dependent. Additionally, p38 has been shown to play a role in regulating both TNF-␣ message stability and protein expression (32,33). We have described previously that Mal interaction with TRAF6 mediates Erk1/2 and JNK activation (17), but not p38, which may explain the discrepancy that the MalE190A mutant is still able to induce TNF-␣ expression.…”
Section: Discussioncontrasting
confidence: 39%
“…Primary inflammatory stimulus may act through membrane receptors such as the TNF-a receptor 1 (TNFR1), which cause the activation of four major intracellular signaling pathways that are cascades of protein kinases, namely the three distinct mitogen-activated protein kinase (MAPK) pathways, p38, Jun-NH 2 -terminal kinase 1 and 2 (JNK1/2) and extracellular signal-regulated kinase 1 and 2 (ERK1/2), and the one leading to activation of the nuclear factor kB (NF-kB). 27 Incubation of astrocytes with 50 mM UCB and 100 mM HSA resulted in a biphasic activation of TNFR1 during the 24 h observation period. 25 The early phase was detected as early as 15 min, peaking at 1 h, and the late phase occurred at 12 h. Although the early-phase activation may result from a direct interaction of UCB with the TNFR1, we speculate that the secondary activation may be attributed to the action of IL-1b and IL-6 produced during astrocyte exposure to UCB (Figure 1), which are known to upregulate TNFR1.…”
Section: Introductionmentioning
confidence: 96%
“…The production of these secreted mediators is stringently regulated at multiple mechanistic levels, including gene transcription, mRNA translation, and ultimately selective degradation of specific mRNAs (5)(6)(7)(8). Hence the pattern of gene expression depends critically upon appropriate engagement of each of these regulatory steps and deficiencies at any specific stage have been demonstrated to profoundly impact normal function (9,10).…”
mentioning
confidence: 99%
“…Hence the pattern of gene expression depends critically upon appropriate engagement of each of these regulatory steps and deficiencies at any specific stage have been demonstrated to profoundly impact normal function (9,10). mRNA degradation is now widely recognized as an important regulatory step in controlling gene expression, and this is particularly true for short lived mRNAs such as those encoding cytokine and chemokine proteins (6,7,11,12). The instability of such mRNAs is determined by sequence motifs frequently located in the 3Ј untranslated region (3Ј-UTR) 1 of the message.…”
mentioning
confidence: 99%
See 1 more Smart Citation